Activated Carbon Addition Methods on the Pre-impregnation Process of Co-Mo in Y-Zeolite Ultra Stable: A Properties Exploration and Enhancement of Metals Loaded - Hidayat, Yuniawan; Nugrahaningtyas, Khoirina Dwi; Hendrastuti, Priska Julia (Universitas Andalas, 2021)
The amount of loaded Co-Mo metal on the Y-Zeolite Ultra Stable (USY) was increased by the addition of activated carbon in the pre-impregnation process. USY modification was done by adding activated carbon to USY as much as 10 wt%. The process of adding activated carbon is carried out by three methods, i.e., grinding with sucrose binder (ACU1), without sucrose (ACU2), and conducting by ball milling (ACU3). Wet impregnation method was employed to disperse the Co and Mo, sequentially. Composites were characterized using Fourier Transform Infrared (FTIR), X-ray diffraction (XRD), and surface area analyzer (SAA). Metal dispersions were observed by X-ray fluorescence (XRF). The FTIR suggests an interaction between USY and activated car-bon, while the XRD result indicated the none structural transformation of USY zeolite. The SAA analysis showed an increased total pore radius with the activated carbon addition. The XRF confirmed the increasing of total metals dispersion of 6.25% (ACU1); 5.48%(ACU2); 5.18% (ACU3); compare to USY origin with 3.28% metals loaded.